X-linked hypophosphatemic rickets and nephrocalcinosis: clinical characteristics of a single-center pediatric cohort in North America before and after burosumab - Paloian, Neil J.; Boyke-Lohmann, Lindsey R.; Steiner, Robert D. (Frontiers in Pediatrics, 2024)
Background: XLH (X-linked hypophosphatemic rickets) is a rare genetic disease characterized by inappropriately elevated circulating FGF-23 and urinary phosphate wasting. The clinical manifestations include short stature, lower extremity bowing, dental abscesses, and rickets. Historical treatment includes phosphate and vitamin D supplementation, but recently therapy with burosumab (an FGF23 blocking antibody) has become available. Conventional therapy options have been associated with the development of nephrocalcinosis (NC) with reported with varying rates in XLH patients. Previous studies have noted that the dose of phosphate supplementation correlates with NC, though there is inconsistency in this finding. It remains unclear whether nephrocalcinosis occurs in patients now treated with burosumab. Our aim was to identify nephrocalcinosis risk factors in our cohort of children with XLH. We identified thirteen children with XLH who received medical care at our institution between 2015-2023. All were treated with conventional therapy and were transitioned to burosumab. Routine monitoring including laboratory tests and renal ultrasonography were obtained on all patients. Medication doses and laboratory values were analyzed between the group with NC versus the group without NC.Results: Three patients were noted to have evidence of NC within the study timeline. Two children developed NC while receiving conventional therapy, and one while prescribed burosumab. None of the variables examined including duration or dosage of treatment with conventional therapy, average age at initiation of burosumab, and all measured laboratory values were significantly different between the group with and without NC. Female sex was the only identified significant risk factor for a diagnosis of XLH associated NC.XLH associated NC remains a clinical concern even with modern treatment, though the traditional risk factors (dose of phosphate supplements and degree of urinary phosphate excretion) may not always correlate with the onset of nephrocalcinosis. XLH patients receiving burosumab, which has been hypothesized to eliminate the risk factors for NC, can still develop NC. It is important to continue to screen patients treated with burosumab for nephrocalcinosis. Additionally, more research is needed to better understand the risk factors that cause XLH associated NC and to determine whether children with XLH never exposed to conventional therapy will develop NC.